PERAN MAKROMINERAL DALAM MENGATASI GANGGUAN REPRODUKSI RUMINANSIA (ARTICLE REVIEW) - Adriani Adriani; Nurul Humaidah; Dedi Suryanto (Dinamika Rekasatwa: Jurnal Ilmiah (e-Journal), 2020)
Ma.kromineral ad.alah sa.lah sa.tu nut.risi ya.ng be.rperan pe.nting da.lam pertu.mbuhan, ke.sehatan, prod.uksi, rep.roduksi da.n kek.ebalan tu.buh he.wan. Ter.nak rum.inansia memb.utuhkan makro.mineral sepe.rti ka.lsium (Ca), fos.for (P), magn.esium (Mg), kali.um (K), nat.rium (Na), klor.ida (Cl) dan sul.fur (S). Ke.butuhan min.eral rumina.nsia dipe.ngaruhi ol.eh bebe.rapa fak.tor sep.erti um.ur, sta.tus kebunti.ngan dan st.atus lak.tasi. Keku.rangan mi.neral sa.lah sa.tu akibat.nya ad.alah dap.at me.ngakibatkan gan.gguan repr.oduksi rum.inansia. Kek.urangan makr.omineral be.rpengaruh te.rhadap kin.erja rep.roduksi rumin.ansia sec.ara lang.sung maup.un ti.dak lan.gsung. Ma.kro.mine.ral berp.engaruh se.cara lang.sung ter.hadap kin.erja fung.si kel.enjar hip.ofisa sehi.ngga wakt.u estru.s d.an o.vulasi me.njadi le.bih lam.a, invo.lusi ute.rus ter.tunda, mening.katnya pr.olaps u.teri, kej.adian disto.kia da.n ret.ensi pla.senta. Peng.aruh ti.dak lan.gsung mel.alui penu.runan fun.gsi sya.raf, penuru.nan naf.su ma.kan, kem.ampuan abs.orsi gl.uksa, min.eral, a.sam ami.no se.rta penur.unan bo.bot ba.dan. Pema.haman ya.ng meny.eluruh tent.ang pe.ran makrom.ineral te.rhadap fung.si re.produ.ksi ru.minansia san.gat diper.lukan a.gar dap.at melak.ukan pen.cegahan mun.culnya gan.gguan reprodu.ksi ak.ibat pember.ian min.eral ya.ng ku.rang tep.at.